Recall and Understanding of Discharge Information in Observation Ward Patients: An Explorative Observational Study - Østen, Kjersti; Menichetti, Julia; Nordfalk, Jenny M.; Ofstad, Eirik H. (Frontiers in Communication, 2021)
Effective communication is essential for understanding and recall of information after patient discharge from a hospital. This study aimed to explore discharge information, patient recall and patient involvement in discharge encounters. We conducted an explorative observational study at a secondary care level, observational ward. Patients discharged to their home were asked to participate. 34 patients were assessed for eligibility, of which 13 were included in the analysis. Multiple sources of data were collected: videotapes of discharge encounters, questionnaires to patients and physicians, and semi-structured interviews with patients two weeks after discharge. All patients were satisfied with the information received. Five of the eight patients discharged with more than one change in medication had only partial or no recall of these changes. In seven of the 13 encounters the patients and physicians did not agree on the main message. The patients were to a small extent involved in decision-making. Our findings highlight the gaps in the information exchange at discharge encounters and the resulting poor information recall among patients. Patients do not seem aware of these gaps. Greater provider awareness of patient involvement in the encounter and inclusion of the patient’s perspective may improve communication, and consequently understanding and recall.